Art of the Flint Hills - Don Lambert (Symphony in the Flint Hills, 2011)
We’ll never know who created the first art of the Flint Hills. It was made, no doubt, hundreds of years ago when a roaming Native American grabbed a piece of flint to etch onto a rock the vastness of the tallgrass prairie as far as he could see and ride.
Keywords: art; Flint Hills; Kansas; Native American; Indians; expedition; sketches; William Fairholme; photographers; Fort Riley; photograph; John Noble; Alexander Gardner; Wabunsee County; Wichita Art Museum; Robert Sudlow; Lawrence; Cottonwood Falls; Judith Mackey; Mark Feiden; Konza Press; prairie